Efficacy and Safety of Transcutaneous Electrical Acupoint Stimulation for Postoperative Pain: A Meta-Analysis of Randomized Controlled Trials. (14th April 2022) - Wang, Dan; Shi, Hongshuo; Yang, Zhenguo; Liu, Wenbin; Qi, Lu; Dong, Chengda; Si, Guomin; Guo, Qi
Abstract : Objective . This meta-analysis aims to evaluate the effectiveness and safety of transcutaneous electrical acupoint stimulation (TEAS) in treating post-operative pain. Methods . This meta-analysis was registered in PROSPERO (CRD42021286753). We searched PubMed, Embase, and the Cochrane Library for relevant randomized controlled trials (RCTs) about TEAS in treating postoperative pain that were published before November 2021. The primary outcome was visual analogue scale (VAS) within 24 h after surgery. The secondary outcomes included postoperative opioid analgesic drug consumption and the occurrence of adverse reactions within the postoperative 24–72 h. Adverse reactions included dizziness, nausea, and vomiting. Continuous variables were analyzed using mean difference (MDs) or standardized mean difference (SMDs) and 95% CIs. Relative risk (RR) and 95% CI were used for dichotomous data. The data were pooled and analyzed by RevMan 5.4 and STATA15.0 software. Results . Seventeen trials with 1375 participants were included. The current results suggested that application of TEAS showed obvious superiority in reducing VAS scores (SMD = −1.51, 95% CI = −2.20∼−0.82, I2 = 96%). Subgroup analysis was performed according to open surgery and minimally invasive surgery. VAS scores were decreased after surgery at 24 h (SMD = −0.84, 95% CI = −1.07∼−0.6, I2 = 96%; SMD = −0.88, 95% CI = −1.02∼−0.75, I2 = 96%). The incidence of postoperative dizziness and nausea and vomiting was significantly lower in the TEAS group within postoperative 24–72 h (RR = 0.48, 95% CI = 0.34∼0.68, I2 = 0%; RR = 0.66, 95% CI = 0.44∼1.01, I2 = 69%; and RR = 0.49, 95% CI = 0.24∼1.00, I2 = 51%). Postoperative opioid analgesics were also reduced in the TEAS group within 72 h after surgery (SMD = −2.10, 95% CI = −3.37∼−0.82, I2 = 96%). Conclusions . TEAS can reduce postoperative pain as well as the incidence of dizziness, nausea, and vomiting and the number of analgesics used after surgery. TEAS is a reasonable modality to incorporate into a multimodal management approach for postoperative pain.